“Can’t Stop, Won’t Stop”: Self-Control, Risky Lifestyles, and Repeat Victimization - Turanovic, Jillian J. (Journal of quantitative criminology, 2014)
Objectives Drawing from lifestyle-routine activity and self-control perspectives, the causal mechanisms responsible for repeat victimization are explored. Specifically, the present study investigates: (1) the extent to which self-control influences the changes victims make to their risky lifestyles following victimization, and (2) whether the failure to make such changes predicts repeat victimization. Methods Two waves of panel data from the Gang Resistance Education and Training program are used ( N = 1,370) and direct measures of change to various risky lifestyles are included. Two-stage maximum likelihood models are estimated to explore the effects of self-control and changes in risky lifestyles on repeat victimization for a subsample of victims ( n = 521). Results Self-control significantly influences whether victims make changes to their risky lifestyles post-victimization, and these changes in risky lifestyles determine whether victims are repeatedly victimized. These changes in risky lifestyles are also found to fully mediate the effects of self-control on repeat victimization. Conclusions Findings suggest that future research should continue to measure directly the intervening mechanisms between self-control and negative life outcomes, and to conceptualize lifestyles-routine activities as dynamic processes.